La remanufactura aplicada en el mantenimiento del transporte integrado para la reducción de costos (2018)
This document presents an approach to remanufacturing, as a tool for reducing maintenance costs in the company Masivo Capital S.A.S, one of the operating companies of the integrated transportation system in the city of Bogotá. Subsequently, the technical parameters of the project are highlighted, which include a detailed description of the remanufacturing process, its broad field of applicability and its relationship with the automotive sector, specifically in the electrical system, focused on the vehicles that provide the public transport service integrated in the Colombian capital, considering some advantages of the adoption of this tool in the maintenance programs of the fleet.